Effect of Temperature and Relative Humidity on the Incubation Period and the Hatching Percentage of Eggs of Pammene theristis Meyrick (Lepidoptera: Tortricidae) - Sharma, Manisha; Singh, K. P. (Indian Forester, 2018)
Pammene theristis Meyrick (Lepidoptera: Tortrlcldae) is a seed and seedling borer of Shorea robusta. The insect has been closely associated with the dying off of new Sal generation and plays a prominent role in regeneration failure in Sal. Surveys were conducted during IVIarch to October 2016 in various localities in and around Dehradun to find the effect of temperature and relative humidity on the oviposition of the borer. The results revealed that number of eggs laid were directly affected by temperature and evening relative humidity and indirectly affected by morning relative humidity. The incubation period was positively correlated with relative humidity in morning only and it is observed to be negatively correlated with maximum and minimum temperature and evening relative humidity. The percentage of hatching of eggs was positively affected by temperature and negatively affected by relative humidity.